Kinetic study of copper removal by rambutan seed - Nor Hazilah Binti Che Hassan (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Rambutan seed, a fruit waste were used to produce biosorbent through environment friendly process. It were washed, dried, blended into powder and used for copper removal. Copper adsorption onto rambutan seed was depended upon the controlling parameters such as pH, contact time, temperature and dosage. Slightly acidic water (pH=6) was found to be suitable for the copper removal using this biosorbent. Equilibrium data were analyzed using the Langmuir and Freudlich isotherms while the adsorption kinetics data were evaluated using pseudo-first-order and pseudo-second-order kinetics model. Adsorption isotherm analysis data fitted well to the Langmuir model where the R is 0.8519. The kinetic experimented data correlated well with the pseudo-second-order kinetic model compared to the pseudo-first-order model where the R is 0.9405. FTIR analysis of rambutan seed have been carried out, to know that hydroxyl group and carbonyl group are responsible for the adsorption of copper ions. The SEM analyses have been used to examine the surface morphology of rambutan seed before and after the adsorption. The surface of biosorbent rough, have irregular pores before the adsorption. After the adsorption, the surface morphology appears smooth and the pore size appears reduced. The results showed that the rambutan seed has potential to be used as biosorbents for the removal of copper ions from aqueous solution.